Detection and Identification of the First Viruses in Chia (Salvia hispanica) - Celli, Marcos Giovani (2014)
Chia (Salvia hispanica), an herbaceous plant native to Latin America, has become important in the last 20 years due to its beneficial effects on health. Here, we present the first record and identification of two viruses in chia plants. The comparison of the complete nucleotide sequences showed the presence of two viral species with the typical genome organization of bipartite New World begomovirus, identified as Sida mosaic Bolivia virus 2 and Tomato yellow spot virus, according to the ICTV taxonomic criteria for begomovirus classification. DNA-A from Sida mosaic Bolivia virus 2 exhibited 96.1% nucleotide identity with a Bolivian isolate of Sida micrantha, and Tomato yellow spot virus showed 95.3% nucleotide identity with an Argentine bean isolate. This is the first report of begomoviruses infecting chia as well as of the occurrence of Sida mosaic Bolivia virus 2 in Argentina.